Application of net-shaped self-glazed zirconia for crown lengthening and restorative treatments using a full digital workflow. (17th November 2021) - Pi, Yixing; Su, Zhikang; Zhong, Mei; Liang, Tingting; Li, Fuyao; Chen, Ding; Liang, Zitian; Ren, Wen; Li, Yuanjing; Luo, Siqi; Huang, Jiangyong; Guo, Lvhua
ABSTRACT: With the recent interest in more efficient, comfortable, precise and minimally invasive surgical procedures and postoperative repairs, such as crown lengthening, there has been increasing research on the application of full digital technology in clinical scenarios. This clinical case describes an approach to crown lengthening and aesthetic restoration in a digital workﬂow using net-shaped self-glazed zirconia crowns. The findings of the study demonstrated the high compatibility of self-glazed zirconia with the full digital process. The presented approach ensured a higher degree of precision in crown lengthening prostheses, improved patient comfort and shortened clinical chairside time while achieving both aesthetic and functional requirements of anterior teeth in a timely and efficient manner.